2013
DOI: 10.1177/0305735612463772
|View full text |Cite
|
Sign up to set email alerts
|

The older, the wiser?Profiles of string instrument teachers with different experience according to their conceptions of teaching, learning, and evaluation

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in: knowledge needed for producing the correct sound. Our main aim is to study the conceptions of teaching-learning held by 53 teachers of string instruments at elementary levels, and to test how they are affected by the variable teaching experience (in three groups: a) less than 7 years; b) 7 to 14 years, and c) more than 14 years). We also want to determine whether these conceptions give rise to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
18

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 42 publications
(97 reference statements)
2
28
1
18
Order By: Relevance
“…More specifically, and focusing on the two extreme positions which are the object of study in this article, the simpler or more direct positions found by those authors are usually associated with symbolic processing of the score, focusing on a conception mainly involving reproduction of the scores (radical epistemological realism) and centred on ‘transmitting’ its explicit contents. They are usually found in teachers with more years of experience (Bautista et al ., ; López‐Íñiguez et al ., ) who tend to show more traditional or direct conceptions of teaching and learning, and students at lower level (López‐Íñiguez & Pozo, ). Conversely, teachers and students with more innovative or constructive profiles are found to focus mainly on referential aspects of music, without ignoring the relevance of lower levels, and showing an epistemic conception of the use of scores which leads them to prioritize teaching their conceptual content and artistic capacities.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, and focusing on the two extreme positions which are the object of study in this article, the simpler or more direct positions found by those authors are usually associated with symbolic processing of the score, focusing on a conception mainly involving reproduction of the scores (radical epistemological realism) and centred on ‘transmitting’ its explicit contents. They are usually found in teachers with more years of experience (Bautista et al ., ; López‐Íñiguez et al ., ) who tend to show more traditional or direct conceptions of teaching and learning, and students at lower level (López‐Íñiguez & Pozo, ). Conversely, teachers and students with more innovative or constructive profiles are found to focus mainly on referential aspects of music, without ignoring the relevance of lower levels, and showing an epistemic conception of the use of scores which leads them to prioritize teaching their conceptual content and artistic capacities.…”
Section: Introductionmentioning
confidence: 99%
“…Las rúbricas estarían insertas en los portafolios. Otros estudios realizados en España se enfocan específicamente en analizar las ideas que tienen los profesores sobre la evaluación como práctica inserta en las actividades de enseñanza y aprendizaje, y con unas finalidades continua, formativa y formadora (p.ej., Bautista et al, 2010;Bautista et al, 2011;López-Íñiguez, Pozo, & de Dios, 2014;.…”
Section: Los Procedimientos De Evaluación De Las Interpretaciones Musunclassified
“…Su practicum ha sido inexistente o de muy escasa duración (en tal caso, realizado en contextos mayormente tradicionales), y sus oportunidades de participar en iniciativas de desarrollo profesional de alta calidad han sido nulas o muy limitadas (Bautista, Yau, & Wong, 2017). Es por ello que muchos docentes instrumentistas han sido prácticamente impermeables a los nuevos enfoques educativos, pese a las innumerables críticas que ha recibido el modelo de conservatorio en los ámbitos académicos de nuestro país (e.g., Bautista, Pérez Echeverría, & Pozo, 2010, 2011Checa, 2004;López-Íñiguez, Pozo, & de Dios, 2014;, incluso pese a las evidencias de que dicho modelo puede llegar a tener efectos negativos en los estudiantes (Burwell, 2006;Musumeci, 2005).…”
Section: Hacia Nuevas Metas Y Narrativas De Investigación En Educacióunclassified
“…Este enfoque investigador, sin duda de orientación más pragmática o aplicada (Bautista, Wong, & Gopinathan, 2015), podría contribuir a una formación más completa e integral del profesorado, una formación que no se limite al dominio del instrumento o conceptos teóricos, sino que tenga siempre en cuenta los hallazgos de las investigaciones más recientes (Ponce de León & Lago, 2009). Está claro una enseñanza musical de calidad implica huir del nocivo e insano modelo de conservatorio y adoptar enfoque más constructivos (e.g., Bautista et al, 2010Bautista et al, , 2011Checa, 2004;López-Íñiguez et al, 2014;. Pero lo que aún no está tan claro, incluso para los propios investigadores, es cómo ayudar a los docentes a mejorar sus concepciones y cambiar sus prácticas.…”
Section: Hacia Nuevas Metas Y Narrativas De Investigación En Educacióunclassified